Synthesis and Characterization of Novel Analogues of Cefpodoxime Proxetil - Reddy, Peketi Rajesh; Musunuri, Sivanadh; Reddy, D. Ramasekhara; Chittala, V. Subrahmanyam; Murthy, P.V.N.S.; Krishnamohan, K. (Asian Journal of Chemistry, 2020)
The present work describes the origin, identification, synthesis, characterization and control of four novel analogues of cefpodoxime proxetil, which are ethyl, methyl, propyl and N-propyl analogues of cefpodoxime proxetil.